Independent and joint effect of relative telomere length and type 2 diabetes on all-cause mortality in American adults - Lan, Beidi; Bai, Yuan; Chang, Xiaoyi; Zhang, Xiaoxia (Frontiers in Endocrinology, 2022)
Objective The joint effect of leukocyte telomere length (LTL) and type 2 diabetes (T2D) on the risk of all-cause death has been sparsely explored. The study designed to examine the joint effect of T2D and LTL on the probability of death in American adults. Methods A cohort of 6862 adults with LTL measurements and with or without T2D from the NHANES 1999-2002 with follow-up information until 2015 was studied. Quantitative PCR was used to measure the length of telomeres relative to standard reference DNA (T/S ratio). Individuals were grouped into three tertiles according to the LTL levels, with the first tertile demonstrating the lowest one and used as the reference group. The effects of LTL and T2D status on death were evaluated using Kaplan–Meier curves along with log-rank test. Three Cox proportional hazards models with adjustment for various confounders were used to examine the links between TL and all-cause death possibility using adjusted hazard ratios (HRs). Results Adults in the sample averaged 45.54 years of age, with 49.51% being male. After a median follow-up period of 14.4 years, 1543 (22.5%) individuals died from all cause. The probability of all-cause mortality was higher among individuals with LTL in the highest tertile than individuals in the lowest tertile (aHR = 0.89; 95%CI: 0.77-1.03); however, the difference did not reach the level of statistical significance (P = 0.11). Conversely, the individuals with T2D had a higher probability of death than individuals without (aHR = 1.26; 95%CI: 1.06-1.50; P = 0.0092). When LTL and T2D status were investigated jointly, subjects in the highest TLT tertile and with T2D had the highest probability of mortality compared with their counterparts (aHR = 1.34; 95%CI: 1.07-1.68; P = 0.0101). However, there was no independent effect of low TLT on mortality as demonstrated among individuals with diabetes (aHR = 1.14; 95%CI: 0.95-1.38; P = 0.1662). Conclusion The joint effect of TLT and T2D was larger than the sum of the independent effects on the risk of all-cause death. Participants with high TLT and diabetes showed the highest possibility of death compared with other groups.